Investigating the effect of TRPV4 inhibition on pulmonary-vascular barrier permeability following segmental endotoxin challenge. (October 2020) - Mole, Sarah; Harry, Anya; Fowler, Andy; Hotee, Sarah; Warburton, Joseph; Waite, Sarah; Beerahee, Misba; Behm, David J.; Badorrek, Philipp; Müller, Meike; Faulenbach, Cornelia; Lazaar, Aili L.; et al.
Abstract: Background: Acute Respiratory Distress Syndrome (ARDS) is associated with increased pulmonary-vascular permeability. In the lung, transient receptor potential vanilloid 4 (TRPV4), a Ca 2+ -permeable cation channel, is a regulator of endothelial permeability and pulmonary edema. We performed a Phase I, placebo-controlled, double-blind, randomized, parallel group, proof-of-mechanism study to investigate the effects of TRPV4 channel blocker, GSK2798745, on pulmonary-vascular barrier permeability using a model of lipopolysaccharide (LPS)-induced lung inflammation. Methods: Healthy participants were randomized 1:1 to receive 2 single doses of GSK2798745 or placebo, 12 h apart. Two hours after the first dose, participants underwent bronchoscopy and segmental LPS instillation. Total protein concentration and neutrophil counts were measured in bronchoalveolar lavage (BAL) samples collected before and 24 h after LPS challenge, as markers of barrier permeability and inflammation, respectively. The primary endpoint was baseline adjusted total protein concentration in BAL at 24 h after LPS challenge. A Bayesian framework was used to estimate the posterior probability of any percentage reduction (GSK2798745 relative to placebo). Safety endpoints included the incidence of adverse events (AEs), vital signs, 12-lead electrocardiogram, clinical laboratory and haematological evaluations, and spirometry. Results: Forty-seven participants were dosed and 45 completed the study (22 on GSK2798745 and 23 on placebo). Overall, GSK2798745 was well tolerated. Small reductions in mean baseline adjusted BAL total protein ( 9%) and neutrophils ( 7%) in the LPS-challenged segment were observed in the GSK2798745 group compared with the placebo group; however, the reductions did not meet pre-specified success criteria of at least a 95% posterior probability that the percentage reduction in the mean 24-h post LPS BAL total protein level (GSK2798745 relative to placebo) exceeded zero. Median plasma concentrations of GSK2798745 were predicted to inhibit TRPV4 on lung vascular endothelial cells by 70–85% during the 24 h after LPS challenge; median urea-corrected BAL concentrations of GSK2798745 were 3.0- to 8.7-fold higher than those in plasma. Conclusions: GSK2798745 did not affect segmental LPS-induced elevation of BAL total protein or neutrophils, despite blood and lung exposures that were predicted to be efficacious. Clinicaltrials.gov identifier: NCT03511105. Highlights: LPS challenge to the lung caused increases in BAL protein and neutrophils. TRPV4 blockade didn't affect LPS-induced increases in BAL protein or neutrophils. Damage to lung tissue might affect use of a urea correction in BAL samples.